1996
DOI: 10.1159/000262130
|View full text |Cite
|
Sign up to set email alerts
|

Caries Experience in Deciduous Dentition of Rural Chinese Children 3–5 Years Old in Relation to the Presence or Absence of Enamel Hypoplasia

Abstract: The association of enamel hypoplasia (EHP) with dental caries of the deciduous dentition was determined in 1,344 rural Chinese children aged 3–5 years. The degree of EHP was determined using a modified DDE Index. Number of decayed, missing, and filled teeth and tooth surfaces were determined for all subjects. Anthropometric assessment of body weight and height was done as an indirect measure of the nutritional status of the children. Results from the study showed that the prevalence of EHP was 22.3% in the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
106
0
23

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(143 citation statements)
references
References 11 publications
14
106
0
23
Order By: Relevance
“…9,30,40 Malnutrition may cause enamel hypoplasia, and just like iron deficiency anemia, it may lead to reduced salivary secretion and low buffering capacity. 7,11,24,35,42,43 Childhood malnutrition is still a major problem in Brazil, especially in the North and Northeast regions, 44 which may contribute to a larger number of decayed teeth in these regions. The mean DMFT (number of deciduous teeth that are decayed, extracted or indicated to be extracted and filled) at the age of five years in the North region is approximately 27% higher than the mean for the Southeast region.…”
Section: Susceptible Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…9,30,40 Malnutrition may cause enamel hypoplasia, and just like iron deficiency anemia, it may lead to reduced salivary secretion and low buffering capacity. 7,11,24,35,42,43 Childhood malnutrition is still a major problem in Brazil, especially in the North and Northeast regions, 44 which may contribute to a larger number of decayed teeth in these regions. The mean DMFT (number of deciduous teeth that are decayed, extracted or indicated to be extracted and filled) at the age of five years in the North region is approximately 27% higher than the mean for the Southeast region.…”
Section: Susceptible Hostmentioning
confidence: 99%
“…ECC is more commonly found in children who live in poverty or in poor economic conditions, 7,11,[24][25][26][33][34][35][36][37] who belong to ethnical and racial minorities, 12,38 born to single Although the habit of dipping the pacifier in sugar is associated with early colonization by Streptococcus mutans in predentate infants, 49 a systematic review did not find any consistent correlation between the use of pacifiers and the development of ECC, regardless of the length of use of pacifiers and of the introduction of sweeteners or not. 50 Cariogenic role of human milk, cow s milk and milk-based formulas in infant feeding…”
Section: Associated Risk Factorsmentioning
confidence: 99%
“…The present results concerning the RBD agree with those reported by other investigators (6,(21)(22)(23) who reported that malnutrition can cause a rise in the prevalence of caries. Various factors may have contributed to the high prevalence of caries found with the use of the RBD, such as enamel malformation due to episodes of malnutrition (24)(25)(26)(27)(28)(29), affected salivary glands (17,23,30,31), and the composition of the diet itself which, in addition to being deficient in proteins, vitamins and minerals, is rich in carbohydrates (10). When comparing the results for different times of animal feeding, we observed that the animals fed 30 days (1A and 2A) presented caries with less prevalence than the animals fed 60 days (1B, 2B), except for groups 3A and 3B.…”
Section: Resultsmentioning
confidence: 99%
“…Os autores encontraram hipoplasia de esmalte em 18,6% das crianças desnutridas, enquanto que, no grupo com ausência de desnutrição, não houve registro dessa alteração. Segundo Li et al 28 , a prematuridade aliada a um baixo peso ao nascer gera uma associação significativa ao desenvolvimento de hipoplasia de esmalte, um importante fator para o início e a progressão da cárie dentária. De fato, Batista et al 29 em trabalho de revisão sobre a alimentação, o estado nutricional e a condição bucal da criança, concluíram que as deficiências nutricionais no período de formação dentária são causas de defeitos na estrutura do dente, tendo potencial para alterar sua forma e atuar na quantidade e na qualidade da saliva, influenciando no processo de formação da cárie dentária.…”
Section: H I P O P L a S I A D O E S M A L T Eunclassified
“…A pesquisa de 1994 confirmou esses achados 41 . Li et al 28 , estudando 1.344 crianças chinesas da zona rural puderam observar que a deficiência nutricional tem um importante impacto no desenvolvimento dentário e suscetibilidade à cárie.…”
Section: á R I E D E N T á R I Aunclassified